Depression, Anxiety, and Quality of Life in Hepatitis C Patients Treated with Direct-Acting Antiviral Agents - Khoshnam-Rad, Niloofar; Kohneloo, Aarefeh Jafarzadeh; Kargar, Mona (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Khoshnam-Rad N, Jafarzadeh Kohneloo A, Kargar M. Depression, anxiety, and quality of life in hepatitis C patients treated with direct-acting antiviral agents. Turk J Gastroenterol. 2022;33(5):449-450.